Differences in the availability of medicines for chronic and acute conditions in the public and private sectors of developing countries - Alexandra Cameron; Ilse Roubos; Margaret Ewen; Aukje K Mantel-Teeuwisse; Hubertus GM Leufkens; Richard O Laing
OBJECTIVE: To investigate potential differences in the availability of medicines for chronic and acute conditions in low- and middle-income countries. METHODS: Data on the availability of 30 commonly-surveyed medicines - 15 for acute and 15 for chronic conditions - were obtained from facility-based surveys conducted in 40 developing countries. Results were aggregated by World Bank country income group and World Health Organization region. FINDINGS: The availability of medicines for both acute and chronic conditions was suboptimal across countries, particularly in the public sector. Generic medicines for chronic conditions were significantly less available than generic medicines for acute conditions in both the public sector (36.0% availability versus 53.5%; P=0.001) and the private sector (54.7% versus 66.2%; P=0.007). Antiasthmatics, antiepileptics and antidepressants, followed by antihypertensives, were the drivers of the observed differences. An inverse association was found between country income level and the availability gap between groups of medicines, particularly in the public sector. In low- and lower-middle income countries, drugs for acute conditions were 33.9% and 12.9% more available, respectively, in the public sector than medicines for chronic conditions. Differences in availability were smaller in the private sector than in the public sector in all country income groups. CONCLUSION: Current disease patterns do not explain the significant gaps observed in the availability of medicines for chronic and acute conditions. Measures are needed to better respond to the epidemiological transition towards chronic conditions in developing countries alongside current efforts to scale up treatment for communicable diseases.